![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
(根号2+根号3-根号6)^2-(根号2-根号3+根号6)^2
1个回答
展开全部
(√2+√3-√6)^2-(√2-√3+√6)^2
=[(√2+√3-√6)-(√2-√3+√6)]
*[(√2+√3-√6)+(√2-√3+√6)]
=[√2+√3-√6-√2+√3-√6]
*[√2+√3-√6+√2-√3+√6]
=[√3-√6+√3-√6]*[√2+√2]
=(2√3-2√6)*2√2
=√3(2-2√2)*2√2
=2√6*(2-2√2)
=4√6-2√2*2√6
=4√6-8√3
=[(√2+√3-√6)-(√2-√3+√6)]
*[(√2+√3-√6)+(√2-√3+√6)]
=[√2+√3-√6-√2+√3-√6]
*[√2+√3-√6+√2-√3+√6]
=[√3-√6+√3-√6]*[√2+√2]
=(2√3-2√6)*2√2
=√3(2-2√2)*2√2
=2√6*(2-2√2)
=4√6-2√2*2√6
=4√6-8√3
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询